OPTIMALISASI PEMANFAATAN APLIKASI SENAYAN LIBRARY MANAGEMENT SYSTEM (SLiMS) PADA PERPUSTAKAAN PERGURUAN TINGGI DI KOTA PEKANBARU - Fitriyana Fitriyana; Triono Dul Hakim; Hadira Latiar (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2021)
The purpose of this study was to determine the optimization of the utilization of the Senayan Library Management System (SLiMS) application in the library in Pekanbaru City. The method used in this research is qualitative. The sampling technique used is purposive sampling, which is sampling intentionally based on officers who are directly involved with the required sample requirements. The results of the study indicate that from several indicators that have been determined, the utilization of the SLiMS application cannot be said to be optimal because the features in the SLiMS application have not been fully utilized. Unilak Library UPT does not take advantage of two features, namely the Inventory feature and serial publication control feature, while the UMRI Library UPT has utilized all the features but there are still some sub-features that are not utilized. Utilization of existing features in the SLiMS application at UPT UMRI Library and UPT Unilak Library is based on the needs and policies of the Library.